Analysis of the Existing Conditions of Balikpapan Permai Market Towards Smart Living Market and SNI Through Revitalization - Sari, Oryza Lhara; Rahmat, Rahmat; Pratama, Maryo Inri; Mustofa, Umar (CIVED, 2023)
Traditional markets are often associated with unhygienic conditions and limited facilities. This makes consumers uncomfortable shopping in traditional markets and results in traditional markets losing out to modern markets. Therefore, it is important for traditional markets to be empowered in order to maintain their sustainability and existence. Balikpapan Permai Market is one of the existing markets in Balikpapan and has various problems related to the quality and physical and non-physical conditions of the market. The purpose of this research is to find out the supporting factors of Balikpapan Permai Market revitalization by using smart living approach and SNI 8152:2021 Pasar Rakyat. Smart living will review in terms of harmony, health, mobility, security, and building, while SNI 8152:2021 Pasar Rakyat will review in terms of general requirements, technical requirements, and management requirements. The method used in this writing is a qualitative method by conducting several stages of research. The results of this research are supporting factors that make Balikpapan Permai Market needs revitalization by reviewing the existing conditions and opinions from the head of UPT market, traders, and market visitors.